Health Descentralization: Conceptual Framework and Public Policies in Argentina - Silvana Moscoso, Nebel (2009)
Some health systems faced difficulties to ensuring equity and efficiency in resource allocation have generated processes reforms including decentralization policies. Argentina implemented: Decentralization of Public Hospitals, Strategy Primary Health Care, Plan Remediar and Provincial Health Insurance. The aim of this work is to analyze the decentralization policies since the economic and administrative approaches. The methodology included: a review of the conceptual framework of decentralization, historical analysis of decentralization in Argentina, description and conceptual analysis of public policies implemented in the ‘90s. In all cases involve policies transfer of administrative responsibilities to subnational levels with the incorporation of the processes, delegation and devolution. From the economic standpoint, the measures prioritized regional demands satisfaction, through the transfer of responsibilities for provision, financing and assurance of some goods and services.